Sensorineural hearing loss and cognitive impairment: three hypotheses - Zhao, He; Wang, Yan; Cui, Limei; Wang, Hanjing; Liu, Sha; Liang, Tiantian; Liu, Dawei; Qiu, Jingjing; Chen, Liang; Sun, Yan (Frontiers in Aging Neuroscience, 2024)
Sensorineural hearing loss (SNHL) is a category of hearing loss that often leads to difficulty in understanding speech and other sounds. Auditory system dysfunction, including deafness and auditory trauma, results in cognitive deficits via neuroplasticity. Cognitive impairment (CI) refers to an abnormality in the brain’s higher intellectual processes related to learning, memory, thinking and judgment that can lead to severe learning and memory deficits. Studies have established a strong correlation between SNHL and CI, but it remains unclear how SNHL contributes to CI. The purpose of this article is to describe three hypotheses regarding this relationship, the mainstream cognitive load hypothesis, the co-morbidity hypothesis, and the sensory deprivation hypothesis, as well as the latest research progress related to each hypothesis.